PENDUGAAN PARAMETER GENETIK PADA PERSILANGAN DIALEL BEBERAPA TETUA CABAI (Capsicum annuum L.) - Dalimunthe, Sri Romaito (Informatika Pertanian, 2015)
High genetic diversity in chili is the basis for a chili breeding program. One of the methods to increase diversity is through crossing. There are several crossing designs in order to produce new varieties, such as diallel crossing. Diallel analysis is a method for studying the inheritance of characteristics from various crossings. The aim of this research was to estimate the genetic parameters, the general combining ability (GCA) and specific combining ability (SCA) of six inbred lines of chili. The research was conducted in November 2008-May 2009 at the Experimental Farm Leuwikopo IPB. Genetic materials used were six inbred lines of chili (IPB C2, IPB C9, IPB C10, IPB C14, IPB C15 and IPB C20) and the F1s of the combination of six inbred lines. The experimental design was Randomized Complete Block Design with a single factor, namely genotype. The number of genotypes were 36 with three replications, so there were 108 units of experiment. The crossing design used was diallel crossing design. The results showed that there were no interaction between genes on the dichotomous height and fruit weight, significant additive effects, the control genes spread unevenly, and relatively high heritability values. Genotype which carried recessive genes the most was IPB C14 and genotype which carried the most dominant genes was IPB C10. IPB C10 showed the highest GCA for dichotomous height and IPB C2 showed the highest GCA on fruit weight. The crossing between IPB C2 x IPB C10 showed the highest SCA for dichotomous height. For fruit weight, crossing of IPB C2x IPB C14 had the highest SCA. Crossing combination of IPB C2 x IPB C14 was the best hybrid.